Monte Carlo Calculation of Fragment Distributions in Nuclear Reactions - A. Deppman; E. Andrade-II; P. C. R. Rossi; F. Garcia; J. R. Maiorino (Science and Technology of Nuclear Installations)
The fragments produced in nuclear reactions for accelarator driven systems (ADS) operation form elements that can have effects on the structure of the reactor. In this regard, the calculation of fragment distributions gives important information for the development of ADS. To obtain those distributions, the Monte Carlo (MC) method is an important tool, and in this work we describe calculations of fragment distributions through a MC code for reactions initiated by intermediate- and high-energy protons and photons on actinide and preactinide nuclei. We study the production of fragments through spallation and fission reactions. The results show good qualitative agreement with experimental data.